Measurement of beauty-strange meson production in Pb-Pb collisions at √sNN = 5.02 TeV via non-prompt D+s mesons - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kroesen, Martin; Nath, Abhishek; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (Physics letters, 2023)
The production yields of non-prompt Ds+ mesons, namely Ds+ mesons from beauty-hadron decays, were measured for the first time as a function of the transverse momentum (pT) at midrapidity (|y|<0.5) in central and semi-central Pb-Pb collisions at a centre-of-mass energy per nucleon pair sNN=5.02TeV with the ALICE experiment at the LHC. The Ds+ mesons and their charge conjugates were reconstructed from the hadronic decay channel Ds+→ϕπ+, with ϕ→K−K+, in the 4<pT<36GeV/c and 2<pT<24GeV/c intervals for the 0-10% and 30-50% centrality classes, respectively. The measured yields of non-prompt Ds+ mesons are compared to those of prompt Ds+ and non-prompt D0 mesons by calculating the ratios of the production yields in Pb-Pb collisions and the nuclear modification factor RAA. The ratio between the RAA of non-prompt Ds+ and prompt Ds+ mesons, and that between the RAA of non-prompt Ds+ and non-prompt D0 mesons in central Pb-Pb collisions are found to be on average higher than unity in the 4<pT<12GeV/c interval with a statistical significance of about 1.6σ and 1.7σ, respectively. The measured RAA ratios are compared with the predictions of theoretical models of heavy-quark transport in a hydrodynamically expanding QGP that incorporate hadronisation via quark recombination.
Online verfügbar: 19. September 2023, Artikelversion: 29. September 2023
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol
Im Titel ist der Buchstabe "s" tiefgestellt sowie das Pluszeichen hochgestellt
*ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, M. Kroesen, Y. Pachmayer, K. Reygers, R. Schicker, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, M.A. Völkl, B. Windelband, A. Yuncu, F. Zanone [und 1011 weitere Personen]
Gesehen am 04.07.2024